PENGARUH KOMPETENSI, QUALITY OF WORK LIFE DAN SARANA PRASARANA TERHADAP KUALITAS HASIL PENELITIAN - supriyadi; Hari Sulistyo; Devi Erlitas (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2022)
The research was conducted to determine and analyze the influence of the competence of researchers on the quality of research results, the effect of quality of work life on the quality of research results, and the influence of infrastructure on the quality of research results. The influence of researcher competence, quality of work life and infrastructure on the quality of research results at Dislitbangal. The research method used is descriptive method with quantitative approach. The total population is 126 people from each Satker/UPT in Dislitbangal, namely; Labinsen, Labinlek, Labinkimat, Labinbair with a total sample of 56 people obtained through the Simple Random Sampling technique using the Slovin formula. Data collection techniques used are questionnaires and documentation. While the data analysis in order to test the hypothesis using the Multiple Linear Regression technique. The results of data analysis conclude that there is a significant influence between the competence of researchers on the quality of research results at Dislitbangal, there is a significant influence between the quality of work life on the quality of research results at Dislitbangal, there is a significant influence between infrastructure and the quality of research results at Dislitbangal. The results of the F test are known, it can be concluded that simultaneously there is a significant influence between the competence of researchers, quality of work life and infrastructure on the quality of research results at Dislitbangal.